Neural similarity and interaction success in autistic and non-autistic adolescents - Kathryn A. McNaughton; Sarah Dziura; Edward P. Lemay; Heather A. Yarger; Elizabeth Redcay (Scientific Reports)
Abstract High-quality social interactions promote well-being for typically developing and autistic youth. One factor that may contribute to the quality of social interactions is neural similarity, a metric which may capture shared perspectives and experiences of the world. The current research investigates relations between neural similarity to peers and day-to-day interaction success as measured through ecological momentary assessment in a sample of autistic and non-autistic youth aged 11–14 years old. Neural similarity was operationalized as the between-participant correlation of participants’ neural response to naturalistic video stimuli in areas of the brain implicated in mental state understanding and reward processing. Neural similarity did not have a main effect on interaction success. However, across the full sample, neural similarity significantly interacted with reported closeness, such that there were more positive relations between neural similarity and interaction success for closer interactions. Neural similarity also marginally interacted with social partner (i.e., interactions featuring peers versus others) to predict interaction success, suggesting more positive relations between neural similarity and interaction success in peer interactions. In addition, non-autistic youth reported significantly better peer interactions than autistic youth. These findings suggest that similarity to one’s peers in neural processing in mentalizing and reward regions is important for understanding interaction success. They also highlight the challenge peer interactions may pose for autistic youth and propose novel links between peer interaction success and the brain’s mentalizing processes.